Bacteriophages in food supplements obtained from natural sources - Kiani, Aysha Karim; Anpilogov, Kyrylo; Dautaj, Astrit; Marceddu, Giuseppe; Sonna, Willy Nelson; Percio, Marcella; Dundar, Munis; Beccari, Tommaso; Bertelli, Matteo (Acta Biomedica Atenei Parmensis, 2020)
Human gastrointestinal tract is colonized by bacteria that constitute the interstinal microbiota. Changes in the microbiota may lead to several chronic disorders. Bacteriophages are viruses that specifically target bacteria. Several food components contain bacteriophages and probiotics. Bacteriophages have a great specificity for harmful bacteria, helping the growth of good bacteria. Because of their qualities, bacteriophages are considered beneficial component of probiotics that target the pathogenic bacteria and support the natural human microbiota.